Production of β -1,3 glucanase from Penicillium oxalicum T3.3 for biocontrol against Colletotrichum gloeosporioides and Neoscytalidium dimidiatum - Khairul Ikhsan, Khairul Asma Salsabilla (2015)
β-1,3 glucanase produced from fungi is an important hydrolytic enzymes which can been used as biocontrol agent against plant-pathogenic fungi. The objectives of this study are to determine the best substrates for β-1,3 glucanase production, to evaluate the cultural conditions which stimulate in vitro production of β-1,3 glucanase and to characterize the β-1,3 glucanase activity and then study the effect of crude β-1,3 glucanase towards fungal hypahe of C. gleosporioides and N. dimidiatum. β-1,3 glucanase production by Penicillium oxalicum T3.3 was investigated using shake flasks under various culture conditions such as different types of carbon and nitrogen sources, initial medium pH, agitation speed and different types of surfactants. The determination of best cultural conditions was carried out by varying and optimizing one variable at a time. The best cultural condition obtained from the shake flask experiment was used for β-1,3 glucanase production in a 2 L stirred tank fermenter where the effect of different impeller speed was investigated. Furthermore, the crude β-1,3 glucanase was characterized to study the enzyme stability. The role of this enzyme in antagonism action against Colletotrichum gloeosporioides and Neoscytalidium dimidiatum, a well-known fungal plant pathogens causing anthracnose disease in dragon fruit also was examined.